Differential Expressions of circRNAs and Regulatory Mechanisms of ceRNA Network in Liver of Wilson’s Disease TX Mice - Chen H; Wang X; Peng N; Pu Y; Ye H; Gui Y; Zhang R; Zhang J (Dove Medical Press, 2024)
Hong Chen,* Xie Wang,* Nian Peng, Yue Pu, Hao Ye, Yu Gui, Rui Zhang, Juan Zhang Department of Neurology, The First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, 230031, People's Republic of China*These authors contributed equally to this workCorrespondence: Juan Zhang, Department of Neurology, The First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, Anhui, People's Republic of China, Email zhangdoumi2019@163.comBackground: Wilson's disease (WD) is a hereditary disorder characterized by an abnormality in copper metabolism. Liver fibrosis, and potentially cirrhosis, induced by copper accumulation are critical factors in the pathogenesis of WD. CircRNAs exhibit high stability and play crucial roles in numerous biological processes.Methods: RNA-seq technology was employed to conduct transcriptome sequencing of the liver from 12 homozygous (TX) mice in the model group (NL group) and 12 wild-type (WT) mice in the control group (N group). Differentially expressed circular RNAs (DE-circRNAs) were identified, and following GO and KEGG analysis, a competitive endogenous RNA (ceRNA) regulatory network was constructed. The identified DE-circRNAs were then randomly validated using RT-qPCR.Results: Utilizing RNA sequencing (RNA-seq), the study identified 54 DE-circRNAs in TX-j mice with WD-induced liver fibrosis model, among which 19 were up-regulated and 35 were down-regulated. GO analysis revealed multiple biological processes, including single-organism process, cellular process, and metabolic process. Further pathway identification using KEGG implicated several pathways, including the HIF-1, PI3K-Akt, AMPK, FoxO, signaling pathway regulating pluripotency of stem cells, phospholipase D, mTOR, Ras, cGMP-PKG, and MAPK signaling pathway, among others. A ceRNA regulatory network was constructed with 20 circRNAs, 7 miRNAs, and 75 mRNAs as crucial core components. Additionally, RT-qPCR validation was performed on randomly selected DE-circRNAs, yielding consistent results (P< 0.05).Conclusion: The findings provide a significant molecular biology foundation for understanding the pathogenesis of liver fibrosis in WD and offer new insights for exploring potential diagnostic and therapeutic targets.Keywords: circRNA, circRNA-miRNA-mRNA, ceRNA, Wilson's disease, liver fibrosis